Optimalisasi Penjualan melalui Digital Marketing - Nurhayarti, Nurhayarti; Sugiyarti, Listya; Hanah, Siti; Asmilia, Nur; Sutandijo, Sutandijo (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2022)
Partners in this PKM program are culinary MSME actors who are members of the Pamulang Estat MSME Community who must survive during the Covid 19 Pandemic. Pempek Mama Dea Pamulang MSMEs and Bundes are members of the Pamulang Estat MSME Community as WUB (New Entrepreneurs) who need to get coaching from several parties including from the academic field to be able to become a better MSME. The purpose of this Community Service activity is to provide insight, training, and assistance such as optimizing the use of digital marketing in product marketing. The urgent problem currently being faced by partners is the lack of awareness and knowledge/insight into the use of digital marketing to support increasing income and surviving the COVID-19 pandemic. Thus, in order to optimize sales through digital marketing, MSME actors need assistance. This Community Service activity uses mentoring and training methods with a service learning approach through material presentations, hands-on practice, and tutorials by the Community Service team face-to-face with strict procedures during the Covid-19 pandemic. Feedback from service activities by filling out questionnaires from participants. The result of the service activity is to market the products of MSME actors by optimizing digital marketing so that income increases. This activity provides benefits for participants, namely MSME actors in obtaining maximum knowledge/insight on product sales activities and can improve income.